POLA PERILAKU REMAJA UNTUK MENANGANI KELUHAN DYSMENORRHOEA DI SMK MUHAMMADIYAH 2 MOYUDAN SLEMAN YOGYAKARTA - Kiki Sandra Novita Sari; Sri Sumaryani; Yanita Trisetyaningsih (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background: Dysmenorrhea is menstrual pain in the lower abdomen to the waist, which is perceived as pain and prickling feeling. It causes disruption of daily activities and learning activities in students. The prevalence of dysmenorrhea in Indonesia reached 64.25%, consisting of 54.89% of primary dysmenorrhea and 9.36% of secondary dysmenorrhea. Objectives: This research was conducted in order to determine the behavioral patterns of adolescents in dealing with health complaints related to dysmenorrhea. Methods: This study was a quantitative research, with descriptive design. The population in this study was second year students of SMK Muhammadiyah 2 Moyudan, consisted of 93 students. The sample were 72 students with purposive sampling technique. Results: Thirty-eight students (52.8%) chose herbal medicine/herbal drinks to reduce complaints of dysmenorrhea. While 23 students (31.9%) chose to take rest at the school health clinic. Conslusion: Most students in SMK Muhammadiyah 2 Moyudan used herbal medicine/herbal to reduce their dysmenorrhea symptoms. Keywords: Behavior, Adolescent, Dysmenorrhea